2021
DOI: 10.1111/1756-185x.14092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for falls in patients with spondyloarthritis: A systematic review

Abstract: Falls are a significant public health issue and pose a huge burden for healthcare resources around the world. 1 The World Health Organization (WHO) reported that "falls are the second leading cause of accidental or unintentional injury deaths worldwide". 2 Complications of falls include severe injuries such as hip fractures 3 which have been shown to be associated with significant functional decline and mortality. 4 Spondyloarthritis (SpA) refers to a group of inflammatory rheumatic conditions, including ankyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The interpretation of this result is that the gender being male or female does not increase the risk of falls because both sexes have the same medical conditions, use the same number of prescribed medications, and do not engage in physical activity. This result is analogous to the result of a study conducted by Lim et al, (2021) that they found there were no significant associations between the risk of fall and with gender. In related to the educational level, the results found that there is no significant association among the risk for fall of the samples participants in the study and their educational level (the pvalue of level of education was 0.423).…”
Section: Table (1)supporting
confidence: 87%
“…The interpretation of this result is that the gender being male or female does not increase the risk of falls because both sexes have the same medical conditions, use the same number of prescribed medications, and do not engage in physical activity. This result is analogous to the result of a study conducted by Lim et al, (2021) that they found there were no significant associations between the risk of fall and with gender. In related to the educational level, the results found that there is no significant association among the risk for fall of the samples participants in the study and their educational level (the pvalue of level of education was 0.423).…”
Section: Table (1)supporting
confidence: 87%
“…A study carried out in older people living in nursing homes found that polypharmacy was associated with fall risk(OR 1.29, 95% CI1.03–1.60) 12 . However, in a 2021 systematic review that investigated the risk factors and falls among patients with spondylarthritis, the author suggested that polypharmacy was not associated with the risk of falls 13 …”
Section: Introductionmentioning
confidence: 99%
“…A recently published review of falls in patients with SpA reported a prevalence of falls during a retrospective 12-month period of 13%–25%. 34 Risk factors for falls in SpA was among others functional limitation, measured by Bath AS Functional Index (BASFI), and reduced spinal mobility, measured by BASMI. A prior study of 40 patients with AS and 40 age-matched and sex-matched controls found a statistically significantly higher proportion with a history of falls in AS (20%) compared with the controls (5%).…”
Section: Discussionmentioning
confidence: 99%